Safety and Efficacy of Tacrolimus Ointment Alone in the Treatment of Pediatric Vitiligo: A Systematic Review and Meta-Analysis - Alshaymaa Abdulrahman Alshaikh; Joud Abdulrahman Alshaikh; Hind Alatawi (Biomedicine Hub)
Introduction: Vitiligo, a skin disorder affecting melanocytes, poses treatment challenges. There is a need to investigate the role of tacrolimus in pediatric cases for its efficacy and safety. The present study aimed to assess the safety and efficacy of tacrolimus ointment in treating pediatric vitiligo patients. Methods: A review study was conducted, and a literature search was done on 2 August 2023, by using the words “vitiligo” and “tacrolimus” through five databases including PubMed. We found 8 studies from 930 records. Results: The rates of excellent, moderate, mild, minimal improvement, and no response were 29% (95% CI: 16–47), 26% (95% CI: 19–35), 28% (95% CI: 20–37), 19% (95% CI: 12–29), and 8% (95% CI: 2–25). No systemic side effects were reported. The overall prevalence of local side effects was 14% (95% CI: 7–24). Burning sensation prevalence was 11% (95% CI: 7–18), while pruritus prevalence was 9% (95% CI: 2–33). Study limitations encompassed varied vitiligo sites, patient demographics, and follow-up durations, lacked comparative treatment data, and necessitated further research on combined therapies, especially in pediatric cases. Conclusion: Tacrolimus showed good efficacy regarding the re-pigmentation improvement in pediatric vitiligo patients. Furthermore, no systemic side effects were reported and local side effects were minimal mainly in the form of a burning sensation and pruritus.